Analisis Strategi Manajemen Pengendalian Logistik di Instalasi Farmasi Rumah Sakit: Scoping Review - Susanti, Lili; Darmawan, Ede Surya (Syntax Literate, 2025)
Effective and efficient pharmaceutical logistics management is a crucial component in ensuring the quality of healthcare services in hospitals. The hospital pharmacy plays a strategic role in ensuring the timely availability of medicines, medical devices, and consumables in the right quantity, quality, and at an efficient cost. However, many hospitals still face challenges such as stock-outs, overstocking, expirations, and weak procurement and distribution systems. This study aims to identify and analyze various logistics management control strategies implemented in hospital pharmacies using a scoping review approach. A systematic literature review was conducted based on the PRISMA-ScR framework by searching articles in databases such as Scopus, ScienceDirect, and ProQuest for publications from 2016 to 2025. Out of 72 identified documents, 10 articles met the inclusion criteria. The results show that logistics control strategies can be categorized into five main approaches: conventional methods (EOQ, ROP), classification-based methods (ABC-XYZ), digital technologies (JIT, RFID), artificial intelligence (AI, Faster R-CNN), and predictive models (MPC). Each strategy presents its own advantages and challenges in terms of cost efficiency, data accuracy, infrastructure readiness, and human resource capacity. This review recommends strengthening logistics information systems, investing in technology, and enhancing human resource capabilities as key pillars to improve the effectiveness and sustainability of pharmaceutical logistics management in hospitals.